Analisis Tingkat Keselamatan Ruas Jalan Tongas-Lumbang Sukapura Kabupaten Probolinggo - Primasworo, Rifky Aldila ; Nugroho, Meriana Wahyu (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Probolinggo Regency is one of the administrative regions in East Java Province which is located on the north coast, with national roads (pantura lanes) running from Surabaya to Banyuwangi and Bali Provinces, and there is also a national strategic road leading to the Bromo mountain . These road segments have high traffic volume and potential to cause traffic accidents. One of the sections in the Probolinggo Regent attachment decree in 2015 is TongasLumbang-Sukapura section of 25 roads whose authority Probolinggo Regency Government. These urban roads that connect between sub-districts in Probolinggo Regency and have diverse land use conditions, and quite a number of activities, which have the potential to cause accidents. To reduce the level of traffic accidents on the Tongas-Lumbang-Sukapura road, it is necessary to pay attention to the safety aspects of road infrastructure and other factors (natural conditions, design of road segments (vertical and horizontal alignment), pavement damage conditions, driver visibility, sign completeness or indicators roads and local regulations / policies.The aim of this study is to analyze and evaluate the safety on Tongas-LumbangSukapura road section (from the physical / geometrical of the road and infrastructure aspects) as well as efforts to handle and provide alternative solutions. According to regulation no. 22 of 2009 concerning about Road Traffic and Transport Safety, it?s obtained that isn?t safe from Geometry / physical and infrastructure aspects. The sollution is from of road geometry aspect, it needs to be improved in 4 (four) aspects, namely the width of the lane, sidewalks, waterways, road pavement while from the aspect of infrastructure, the addition of road markings, monitoring equipment and supporting facilities.